2020
DOI: 10.20964/2020.02.12
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition Effect of Three Imidazolium Ionic Liquids On Carbon Steel In Chloride Contaminated Environment

Abstract: Three imidazolium-type ionic liquids, substituted with polar groups at N1 and alkyl chains at N3 were synthesized under mild reaction conditions. The corrosion inhibition of carbon steel in 0.3 M NaCl saturated Ca(OH)2 solution was investigated. Influence of concentration corrosion inhibition effectiveness was obtained by potentiodynamic polarization and electrochemical impedance spectroscopy. Imidazolium ionic liquid acted as a mixed type of inhibitor by both chemical and physical adsorption on the steel surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…First, mono‐6‐( p ‐toluenesulfonyl)‐β‐CD was obtained according to [42] and described earlier [43]. Second, N ‐butylimidazole was synthesized based on [44] and was characterized by a refractive index at 22°C (in agreement with data from the literature [45]). In the end, the white solid of 1‐Bu‐3‐β‐CD‐ImOTs was a product of the mixing of mono‐6‐( p ‐toluenesulfonyl)‐β‐CD and N ‐butylimidazole.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…First, mono‐6‐( p ‐toluenesulfonyl)‐β‐CD was obtained according to [42] and described earlier [43]. Second, N ‐butylimidazole was synthesized based on [44] and was characterized by a refractive index at 22°C (in agreement with data from the literature [45]). In the end, the white solid of 1‐Bu‐3‐β‐CD‐ImOTs was a product of the mixing of mono‐6‐( p ‐toluenesulfonyl)‐β‐CD and N ‐butylimidazole.…”
Section: Methodsmentioning
confidence: 94%
“…Preconcentration was based on a change in the effective electrophoretic mobility direction of the analytes. However, this effect was caused by the presence of organic solvent in BGE, while we propose to use the variation of the analyte ionization forms [44]. First of all, the capillary was filled with BGE (pH 6.4) containing 1 mM 3-Bu-1-β-CD-ImOTs.…”
Section: Online Preconcentrationmentioning
confidence: 99%
“…Similarly, Zhang [ 51 ] showed that the corrosion inhibition efficiency of 1-R-2-undecyl imidazoline compounds was in the order of CH 2 COOH (A) > CH 2 CH 2 OH (B) > CH 2 CH 2 NH 2 (C) > H (D)) for carbon steel, which is consistent with the decrease sequential of the Hammett substituent constants as exhibited in Table 3 , suggesting that the stronger the electron-withdrawing ability of the group connected to the parent, the stronger the corrosion inhibition performance of the entire N-heterocyclic molecule. Additionally, Cai et al [ 52 ] investigated three imidazole-based ionic liquids substituted by polar groups (-COO − ,-Ph) at N1 in 0.3 M NaCl-saturated Ca(OH) 2 solution. It was found that the corrosion inhibition effect of the carboxyl substituent (electron-withdrawing group) was better than that of the phenyl substituent (electron donating group).…”
Section: The Correlation Between Molecular Structure and Corrosion In...mentioning
confidence: 99%
“…However, there are still some problems with these common methods, such as increasing the shrinkage of concrete, affecting workability, and making dispersion difficult in highly aggressive environments. Currently, hydrophobic- or superhydrophobic-modified cement-based material has obtained widespread attention because of its excellent medium transmission resistance and great application potential [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. The hydrophobic methods of concrete include surface hydrophobic and integral hydrophobic treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Integral hydrophobic treatment has the advantage of not being easily affected by surface erosion, so this technique has been widely studied in recent years. Fatty acid and silane emulsion are both typical internal hydrophobic substances; in addition, hydration-responsive nano-materials or smart polymers can also be considered as newly hydrophobic admixtures [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. The integral hydrophobic treatment can reduce water absorption approximately 80%, decreasing the aggressive ions’ permeability and improving the corrosion resistance of cement-based materials.…”
Section: Introductionmentioning
confidence: 99%